Fabrication and electrical properties of lead zirconate titanate-cement-epoxy composites - R. Rianyoi (2018)
In this study, epoxy modified lead zirconate titanate-cement 0-3 and 1-3 composites were fabricated via two different techniques with epoxy added as the third phase. The 0-3 composites were fabricated by the normal paste mixing, while the 1-3 composites were fabricated using a dice-and-fill technique. The dielectric and ferroelectric properties of the composites were examined. The results showed that dielectric constant (εr) at frequency of 1 kHz of 1-3 composites was higher and dielectric loss was lower than those of the 0-3 composite. The ferroelectric hysteresis loops agree with the results showing reduction area in lossy characteristic and the loops become more apparent in 1-3 composites. The use of epoxy results in a lower Pirvalue but a reduction in the lossy appearance of P-E loops is observed.